The real-time PCR targeting the phage terminase (terL) is not suitable for diagnostics of human Borrelia infections in Europe - Manja Zimmermann; Gabriele Margos; Christine Hartberger; Reto Lienhard; Anna J. Henningsson; Malin Lager; Mateusz Markowicz; Anna-Margarita Schötta; Andreas Sing; Benoit Jaulhac; Per-Eric Lindgren; Alje P. van Dam; et al. (Ticks and Tick-Borne Diseases, 2025)
Bacteria of the Borrelia burgdorferi sensu lato (sl) species complex can cause Lyme borreliosis (LB) in humans. PCR plays an important role in the diagnosis of many infectious diseases but it is used auxiliary in LB diagnostics. Here, we re-analysed a previously published real-time PCR targeting the multicopy gene of the large subunit of phage terminase (terL) in Borrelia. We analysed cultured material of Borrelia burgdorferi sl species, serum and clinical tissue samples of LB patients. PCR conditions were as previously described by Shan et al. 2021 but we also investigated PCR modifications.PCR on cultured specimens showed that whilst all samples of B. burgdorferi sensu stricto (ss) gave a positive result, not all isolates of Borrelia species causing LB in Europe (i.e. B. afzelii, B. garinii) were detected by the terL PCR. Only slight differences in Ct values were detected between PCR runs using the original ZEN/IFBQ double quencher probe compared to other double quencher probes or single quencher probes. Contrary to the hypothesis expressed by the authors of the original paper that the PCR could detect phage DNA in serum, our data show that the terL PCR was negative on all tested serum samples of individuals diagnosed with proven LB. Furthermore, using patient’s tissue samples not all infections with B. afzelii or B. garinii were detected, similar to the results obtained with cultured material or serial DNA dilutions of Borrelia species. We conclude, that the terL PCR in its current form is unsuitable for LB diagnosis in Europe.